Enhancing low-temperature characteristics of graphite anode by comprehensive modification of electrolyte - Makpal Rakhatkyzy; Ayaulym Belgibayeva; Gulnur Kalimuldina; Arailym Nurpeissova; Zhumabay Bakenov (Electrochemistry Communications, 2023)
The performance of lithium-ion batteries is significantly deteriorated at low temperatures due to the components’ properties limitations such as the electrolyte viscosity increase and freezing accompanied with a decrease in ionic conductivity, rise of charge transfer resistance, and a substantial capacity loss (over 50 % of room-temperature capacity) in batteries with commercial electrolytes and graphite anodes, even at 0 °C. In this work, a complex modification of lithium salt and solvents of the electrolyte was applied simultaneously to develop an optimal electrolyte system with improved low-temperature characteristics for a Li/graphite half-cell. Various concentrations of commercial and alternative lithium salts (lithium hexafluorophosphate and lithium difluoro(oxalato)borate), dissolved in a mixture of solvents, were studied as electrolytes to determine the best interaction with a graphite electrode at low temperature. A solvent mixture of non-carbonate, low-freezing-point, organic ester ethyl acetate and solid electrolyte interphase (SEI) forming fluorinated co-solvent fluoroethylene carbonate in a ratio of 9:1 was used to prevent freezing of the electrolyte and ensure the formation of a more conductive SEI layer, respectively. The Li/graphite half-cell with the designed electrolyte system has retained about 80 % of its room-temperature capacity at −20 °C, demonstrating a new perspective for the development of low-temperature type electrolytes.